ELECTROMAGNETIC IRRADIATION WITH EXTREMELY HIGH FREQUENCIES EFFECT STUDY ON LIPID FREE-RADICAL OXIDATION IN WHEAT SEEDLINGS BY CHEMILUMINESCENCE METHOD (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
In this work the effect of electromagnetic irradiation by extremely high frequencies on free-radical reactions accompanied by a weak luminescencechemiluminescence (oxidation process of lipids, intensity of spontaneous chemiluminescence) and malonic dialdehyde accumulation in wheat has been studied. It was shown that this irradiation impacts on lipids oxidation of cellular membranes of both plant seedlings and roots and leads to intensity increasing of free-radical processes. It was also shown that biological system is extremely sensitive to external effect of electromagnetic irradiation, particularly at 50.3 and 51.8 GHz frequencies, which correspond to own resonant frequencies of water molecule oscillations.
Keywords: wheat seedlings and roots, electromagnetic irradiation water resonant frequencies, spontaneous chemiluminescence